Peer review of the pesticide risk assessment of the active substance dimethyl disulfide. (25th November 2019) - ,; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State France for the pesticide active substance dimethyl disulfide are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative uses of dimethyl disulfide as a nematicide, fungicide and herbicide on carrot (field use) and on tomato (greenhouse application). The reliable endpoints, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.